1995
DOI: 10.1002/rcm.1290091420
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation of organic molecules from frozen matrices

Abstract: The technique of frozen matrix-assisted laser ablation coupled with resonance-enhanced multiphoton ionization and reflectron time-of-flight mass spectrometry was used to detect intact organic molecules directly from solutions. When frozen at the temperature of liquid nitrogen, the matrices of interest were ablated by a pulsed C 0 2 single-mode laser. The analyte molecules emerging from the ablated plume were then ionized by a tunable XeCl excimer laser-pumped dye laser and analysed with a gridless reflectron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Indeed, recently a number of new developments have been reported. [22][23][24][25][26][27][28][29][30][31][32] Successful experiments have been reported in which TPD has been combined with vacuum UV (VUV) single photo-ionisation time-of-flight mass spectrometry (TOF-MS), measuring the mass from desorbing species from the ice. 22,23 Diagnostic techniques such as Substrate/Matrix Assisted Laser Desorption Ionisation Time-ofFlight Mass Spectrometry ((S/M)ALDI-TOF-MS) have been introduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recently a number of new developments have been reported. [22][23][24][25][26][27][28][29][30][31][32] Successful experiments have been reported in which TPD has been combined with vacuum UV (VUV) single photo-ionisation time-of-flight mass spectrometry (TOF-MS), measuring the mass from desorbing species from the ice. 22,23 Diagnostic techniques such as Substrate/Matrix Assisted Laser Desorption Ionisation Time-ofFlight Mass Spectrometry ((S/M)ALDI-TOF-MS) have been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Diagnostic techniques such as Substrate/Matrix Assisted Laser Desorption Ionisation Time-ofFlight Mass Spectrometry ((S/M)ALDI-TOF-MS) have been introduced. 26,27,31 In the case of the MALDI-technique, a laser is used to desorb large molecules by exciting vibrational modes of the matrix molecules in which the molecules of interest are embedded. A similar approach was recently applied, to investigate radiation-induced processes of Polycyclic Aromatic Hydrocarbons (PAHs), embedded in interstellar ice analogous, using Resonant Enhanced Multi Photon Ionisation (REMPI) as ionisation source.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] More recently, progress in other types of desorption techniques such as 252-Cf plasma desorption, laser desorption and matrix-assisted laser desorption/ionisation (MALDI), has brought about a series of reports on sputtering of biomolecules from frozen water-containing matrices. [34][35][36][37][38][39][40][41][42][43] The impressive successes of mass spectrometry in "ambient" molecular biology, as well as the potential of LT techniques, inspired the Mass Spectrometric Laboratory of the Institute for Low Temperature Physics and Engineering of the National Academy of Sciences of Ukraine to initiate, in 1992, work on the application of mass spectrometry to problems of cryobiology and cryobiophysics. [44][45][46][47][48][49][50][51][52][53][54][55] In the course of the initial studies the unique possibilities of LT secondary emission mass spectrometry were revealed, which appeared not to be limited solely to analytical chemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…5 8 Values for the 0 K M +-C& bond energies were in good agreement with theoretical predictions. Rate coefficients were determined for gas-phase reactions of Fe', coordinated to the p-donating ligands C2H,, c-C,H,, C,H, and with N,O and C0.15' Association reactions of Al+ with C,H,, C,H,D, [1,3,5]-C,H,D, and C,D, have been studied by FTMS. ',' Several rate constants were found to correlate with the deuterium content of the benzenes.…”
Section: Fullerenesmentioning
confidence: 99%
“…74 Ion-dipole complex formation from deprotonated phenol fatty acid esters has been evidenced by using gas-phase labelling combined with tandem mass spectrometry.' 7 5 Tropylium ion formation from toluene has been thoroughly reviewed. '76 The mechanism of gas-phase aromatic nitration by protonated methyl nitrate has been studied by FTMS.177 Clarifying a long standing ambiguity, the results characterize the nitrating agent as in essence a nitronium ion solvated by a methanol molecule.…”
Section: Fullerenesmentioning
confidence: 99%